Running cultures : racing in time and space - Bale, John (Sport in the global society., 2004)
Running is one of the world's most widely practised sports and recreations. This book 'reads between the lines' of both running and some of its textual and visual representations. It deals with the runner's body and also with the globalisation of running and its practitioners. Although it focuses mainly on serious running, it also examines alternative forms of the sport such as jogging. Drawing on a variety of sources including literature, poetry, art, sculpture, statistics and training manuals, Running Cultures breaks new ground in several ways. It introduces the work of the renowned humanist.